Explaining parasite aggregation: more than one parasite species at a time. Issue 4 (March 2017) - Morrill, André; Dargent, Felipe; Forbes, Mark R.
Graphical abstract: Highlights: Parasite-centric models are used to explore the effects of aggregation on coinfection. Aggregation increases the probability and intensity of conspecific co-occurrence. Aggregation lowers the probability, intensity and diversity of heterospecific infection. In light of the results, generalizable adaptive benefits of aggregation are suggested. Abstract: Studies generally have neglected parasite-centric views in explorations of whether the oft-seen patterns of parasite aggregation are adaptive. Using simulation models, we explored the effects of aggregation on coinfection with hetero- or conspecific parasite species characterised by different mean abundances. Increasing aggregation increased the probability of conspecific co-occurrence for parasites with low mean abundances, and increased median numbers of conspecifics for all species. In comparison, increasing aggregation generally decreased the probability, intensity and diversity of heterospecific co-occurrence, irrespective of mean abundance. Researchers should weigh the respective costs and benefits of increasing co-occurrence with conspecifics and decreasing coinfection with heterospecifics in explaining aggregation.